Measuring monetary policy - Ben S. Bernanke; Ilian Mihov (Institute for Advanced Studies (IHS), 1995)
Extending the approach of Bernanke and Blinder (1992), Strongin (1992), and Christiano, Eichenbaum, and Evans (1994a, 1994b), we develop and apply a VAR-based methodology for measuring the stance of monetary policy. More specifically, we develop a semi-structural VAR approach, which extracts information about monetary policy from data on bank reserves and the federal funds rate but leaves the relationships among the macroeconomic variables in the system unrestricted. The methodology nests earlier VAR-based measures and can be used to compare and evaluate these indicators. It can also be used to construct measures of the stance of policy that optimally incorporate estimates of the Fed's operating procedure for any given period. Among existing approaches, we find that innovations to the federal funds rate (Bernanke-Blinder) are a good measure of policy innovations during the periods 1965-79 and 1988-94; for the period 1979-94 as a whole, innovations to the component of nonborrowed reserves that is orthogonal to total reserves (Strongin) seems to be the best choice. We develop a new measure of policy stance that conforms well to qualitative indicators of policy such as the Boschen-Mills (1991) index. Innovations to our measure lead to reasonable and precisely estimated dynamic responses by variables such as real GDP and the GDP deflator. – – In Erweiterung der Beiträge von Bernanke und Blinder (1992), Strongin (1992) und Christiano, Eichenbaum und Evans (1994a, 1994b) stellen wir eine VAR-Methode zur Messung des jeweils vorherrschenden geldpolitischen Ansatzes vor. Wir entwickeln eine semi-strukturelle VAR, die aus Daten über Bankreserven und die Federal Funds Rate Informationen über die Geldpolitik extrahiert, aber die Beziehungen zwischen den makroökonomischen Variablen im System unrestringiert läßt. Die Methode integriert frühere VAR-gestützte Ansätze und kann verwendet werden, um diese Indikatoren zu vergleichen und zu bewerten. Sie eignet sich auch zur Konstruktion von Maßen über den Stand der Geldpolitik, welche die Schätzungen für die Zentralbankoperationen in jeder Periode in optimaler Weise berücksichtigt. Wir finden, daß unter den existierenden Ansätzen auf die Federal Funds Rate wirkende Schocks (Bernanke-Blinder) ein gutes Maß für die Politikinnovationen in den Perioden 1965-79 und 1988-94 darstellen. Für die gesamte Periode 1979-94 scheinen Schocks auf die Komponente der frei verfügbaren Reserven, die orthogonal zu den Gesamtreserven sind (Strongin), die beste Wahl zu sein. Wir entwickeln eine neues Maß für den Stand der Geldpolitik, welches gut mit qualitativen Indikatoren wie dem Boschen-Mills-Index (1991) übereinstimmt. Schocks auf unser Maß führen zu vernünftigen und präzis geschätzten dynamischen Reaktionen von Variablen wie reales GDP und GDP Deflator.
Keywords: E52; 330; monetary policy; monetary policy stance; semi-structural VAR approach